Critical discourse and semiotic analyses of the changes in the roles and representations of women in action movies across three eras of Hollywood - Abdali Dehchenari, Maryam (2014)
Movies have power beyond pure entertainment; they communicate images of female characters that perpetuate unrealistic, stereotypical, and limiting perceptions. Since the inception of cinema, women have been portrayed in typical roles that show them as under-represented and invisible. This study examines changes of women’s roles and representations in action movies and movie posters across three eras of Hollywood: classical, post-classical, and new Hollywood. Fairclough’s (1995) and Kress and van Leeuwen’s (1996) social semiotic as analytical tools are employed to look at the micro and macro levels of movies and movie posters texts. Lakoff’s (1975) approach helps to analyze female characters’ language. The basic theories of gender stereotype and feminist film are guiding this research. The research investigates female roles in 40 action movies and accompanying posters from 1930 to 2012, with the following objectives: (1) to explore the roles played by women in Hollywood action movies (2) examine how women’s roles are constructed verbally and non-verbally in Hollywood action movies, (3) to investigate the significant changes in women’s role across three eras of Hollywood, and (4) to relate the representation of women in movies and posters to the social, political and economic forces of each era of Hollywood. Based on the analysis of the sample, seven main themes were identified for the roles: (i) occupational, (ii) romantic and erotic, (iii) major, supporting and minor roles, (iv) familial roles, (v) roles reflecting independence and dependence, (vi) roles related to authority and subservience, and (vii) roles depicting good and evil. Findings show that over time, women have had the opportunity to play roles reflecting a greater variety of professional occupations. Romance and eroticism have prevailed over all three eras; however, romantic and erotic roles for women have become more multifaceted in the new Hollywood era. Post-classical movies contained the highest number of erotic roles, demeaning women with nudity and seductive poses were seen in the post-classical movie posters. Female characters in main and supporting roles grew from more passive to more active over time. In the new era, movies showed the most number of women in supporting roles and their images did not find much equity with male hero in terms of size and classificational level in movie posters. In minor roles, women were common citizens with no significant professions in the first two eras while the new Hollywood reserved more prestigious positions for female characters in minor roles; however, verbally, they were muted across three eras. Women in familial roles showed dichotomous representations across three eras, movies showed these characters in passive and sick versus active and supporting roles. Women also became more aggressive and violent in some of familial roles in the new era. With regard to roles depicting dependence and independence, women retained active speaking parts in the classical and new Hollywood eras, but they started to show some active reactions to villains in recent movies. The new era showed the highest number of independent roles in which women had supernatural powers, as well as assertive words and behaviors. Women played authority roles with a humanistic approach in the new era, while they had soft romantic or lusty depiction in the classical movies, their villainy characters were more emphasized in the postclassical period. Women also continued to play subservient roles in all three eras, in which female characters remained passive. The more recent movies have portrayed good women in roles in which they possess supernatural powers and fight as errorless warriors. In the new Hollywood movies, women play evil characters using their intelligence for more criminal intentions, as well as characters with a tendency towards doing good deeds. The findings show that women’s roles in action movies have been impacted on by socio-political and economic forces throughout the three eras. In the classical and post-classical eras, particularly in movies revolving around the themes of war or communism, women found villainous, alluring or dependent identities. In the New Hollywood era, they were cast more as intellectual figures and warriors. The impact of the women’s liberation movement resulted in the representation of sexually aggressive or villainous characters in the post-classical era. In addition, women are often cast as equals with men in independent roles in the new era. In movies centered on terrorist ideology, women have moved from passive and dependent roles to being in an active supporting role. In general, the new Hollywood showed more positive representations and roles of women in terms of being more intelligent and showing more physical prowess in both movies and movie posters. Ethnic representation became more positive in the new Hollywood era. Findings of this research help to create awareness of the dynamic patterns of typification of women in movies and movie posters.